Comparative Transcriptomics of the Bovine Apicomplexan Parasite Theileria parva Developmental Stages Reveals Massive Gene Expression Variation and Potential Vaccine Antigens - Atchou, Kodzo; Ongus, Juliette; Machuka, Eunice; Juma, John; Tiambo, Christian; Djikeng, Appolinaire; Silva, Joana C.; Pelle, Roger (Frontiers in Veterinary Science, 2020)
Theileria parva is a protozoan parasite that causes East Coast fever (ECF), an economically important disease of cattle in Africa. It is transmitted mainly by the tick Rhipicephalus appendiculatus. Research efforts to develop a subunit vaccine based on parasite neutralizing antibodies and cytotoxic T-lymphocytes have met with limited success. The molecular mechanisms underlying T. parva life cycle stages in the tick vector and bovine host are poorly understood, thus limiting progress toward an effective and efficient control of ECF. Transcriptomics has been used to identify candidate vaccine antigens or markers associated with virulence and disease pathology. Therefore, understanding how genes are expressed and where their products act in the pathogenic and infective forms of T. parva should shed more light on host-pathogen interactions in ECF and identify genes underlying difference in parasite stages as well as novel therapeutic targets. Recently, the first gene expression profiling of T. parva was conducted for the sporoblast, sporozoite and schizont stages. Sporozoite is infective to cattle whereas schizont is the major pathogenic form of the parasite. The schizont can differentiate into piroplasm which is infective to the tick vector. The present study was designed to extend the T. parva gene expression profiling to the piroplasm stage with reference to the schizont. Pairwise comparison revealed that 2,740 of a possible 4,084 protein coding genes were differentially expressed, with 1,407 (51%) genes up-regulated and 1,333 (49%) downregulated in the schizont relative to the piroplasm. In addition, over 160 genes were stage-specifically expressed. In general, there were more molecular functions, biological processes, subcellular localizations and pathways significantly enriched in the piroplasm than in the schizont. Using known antigens as benchmarks, we identified several new potential vaccine antigens, including TP04_0076 and TP04_0640, which were highly immunogenic in naturally T. parva-infected cattle. All the candidate vaccine antigens identified are yet to be investigated for their capacity to induce protective immune response against ECF.